2022
DOI: 10.1109/access.2022.3227034
|View full text |Cite
|
Sign up to set email alerts
|

Dual Polarized, Multiband Four-Port Decagon Shaped Flexible MIMO Antenna for Next Generation Wireless Applications

Abstract: A compact, dual polarized, multiband four-port flexible Multiple Input Multiple Output (MIMO) antennae with the connected ground and high isolation is designed with computation and experimental measurement studies. All four monopole radiators are embedded decagon-shaped flexible FR-4 substrate with an outer radius of 10 mm in order to accomplish circularly polarized (CP) radiations, bandwidth enhancement, and compact size of only 45×38×0.2 mm 3 (0.375λ × 0.316λ × 0.0016λ, at lowest resonating frequency 2.5GHz)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The TARC plot for various phased angles between antenna 1 and antenna 2 of the suggested uniplanar structure is displayed in Figure 15. Here, the TARC value is significantly below −10 dB within the operating frequencies, which fulfills the performance standards for MIMO 30 . Also, the suggested MIMO antenna's TARC is unaffected by the scattering environment.…”
Section: Quad Mimo Results and Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The TARC plot for various phased angles between antenna 1 and antenna 2 of the suggested uniplanar structure is displayed in Figure 15. Here, the TARC value is significantly below −10 dB within the operating frequencies, which fulfills the performance standards for MIMO 30 . Also, the suggested MIMO antenna's TARC is unaffected by the scattering environment.…”
Section: Quad Mimo Results and Discussionsupporting
confidence: 56%
“…Here, the TARC value is significantly below À10 dB within the operating frequencies, which fulfills the performance standards for MIMO. 30 Also, the suggested MIMO antenna's TARC is unaffected by the scattering environment.…”
Section: Miniaturized Quad Mimo Diversity Performance Analysismentioning
confidence: 99%
“…From the observation of the Figure 11c, it is found that the magnitude ratio (E x /E y ) is nearly equal to 1 for the designated band, and the phase difference between the E x and E y is almost 90 , which justify the circular polarization attributes of the proposed model. 18,19 Small differences in the S-parameters and axial ratio are the consequence of the incorporation of mm-wave connections, lack of measurement precision, and the influence of manufacturing tolerance. The simulated and measured RHCP/LHCP plots for the proposed metasurface suspended MIMO antenna for ports 1 and 2 at 28 GHz are shown in Figure 12a,b, respectively.…”
Section: Simulated/measured Results and Discussionmentioning
confidence: 99%
“…26 It shows how much power is reflected compared to how much power is incident as a whole. Equation (19) shows how to figure out the value of this parameter for a MIMO antenna with two ports. It is also used to find the values of TARC under different theta values.…”
Section: Diversity Performance Parametersmentioning
confidence: 99%
“…To realize the integration of multiple functions, it is required to use the multimode and multifrequency antenna to satisfy the multiservice requirement of terminals. Multimode and multifrequency can be achieved by loading slots, stubs, and parasitic elements [7][8][9][10][11], which has the advantages of small size and easy feeding, but often results in pattern distortion or beam splitting. Te other way is to use separate antennas arranged side by side or embedded for each band and mode [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%